2014
DOI: 10.1095/biolreprod.114.123794
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Specific Stem Cells in the Myometrium and Tumor-Initiating Cells in Leiomyoma1

Abstract: Tissue-specific (or somatic) stem cells constitute a subset of cells residing in normal adult tissues. By undergoing asymmetric division, they retain their ability to self-renew while producing daughter cells that go on to differentiate and play a role in tissue regeneration and repair. The human uterus consists primarily of endometrium and myometrium (the smooth muscle layer) that rapidly enlarges through its tremendous regenerative and remodeling capacity to accommodate the developing fetus. Such uterine enl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 81 publications
0
42
0
5
Order By: Relevance
“…By regulating adult stem cell signaling pathways (e.g., Wnt, Notch), KLFs may similarly control the regenerative capacity of endometrial and myometrial stem/progenitor cells. In this regard, endometriosis (Sassoon & Taylor 2008) and leiomyoma (Ono et al ., 2014) are increasingly considered to be a consequence of deregulated stem cell expansion. Indeed, endometrial epithelial stem/progenitor cells have been characterized from eutopic endometrium of women with endometriosis (Li et al ., 2014), ovarian endometriotic cysts (Chan et al, 2011), endometrial carcinoma tissues (Hubbard et al, 2009) and uterine leiomyoma (Ono et al, 2012).…”
Section: Klfs and Targeted Signaling Pathways In Uterine Pathologiesmentioning
confidence: 99%
“…By regulating adult stem cell signaling pathways (e.g., Wnt, Notch), KLFs may similarly control the regenerative capacity of endometrial and myometrial stem/progenitor cells. In this regard, endometriosis (Sassoon & Taylor 2008) and leiomyoma (Ono et al ., 2014) are increasingly considered to be a consequence of deregulated stem cell expansion. Indeed, endometrial epithelial stem/progenitor cells have been characterized from eutopic endometrium of women with endometriosis (Li et al ., 2014), ovarian endometriotic cysts (Chan et al, 2011), endometrial carcinoma tissues (Hubbard et al, 2009) and uterine leiomyoma (Ono et al, 2012).…”
Section: Klfs and Targeted Signaling Pathways In Uterine Pathologiesmentioning
confidence: 99%
“…Tissue-specific stem cells have been identified in a variety of tissues and organs (99). The presence of a myometrial stem cell (MSC) population in the uterus was first shown in 2007 in mouse myometrium and non-pregnant human myometrium, using 5-bromo-2′-deoxyuridine and sorting of a side population, respectively (89,100).…”
Section: Stem Cells and The Origin Of Uterine Fibroidsmentioning
confidence: 99%
“…One principal difference between MSCs and TICs at the DNA level is that MED12 mutations are found only in UF TICs, but not normal myometrium or MSCs (90). TICs derived from UFs have stem cell characteristics, and are proliferative, give rise to tumors in vivo (90,95) and comprise~1% of UF cells, (99). Similar to MSCs, TICs express low levels of ER and PR, although they are paradoxically dependent on estrogen/progesterone for growth (90,102).…”
Section: Stem Cells and The Origin Of Uterine Fibroidsmentioning
confidence: 99%
“…17 UF growth and progression depend on a specialized subpopulation of tumor cells, termed tumor initiating cells (TICs). 3,23 Thus, TICs represent a critical therapeutic target, but the molecular mechanisms that regulate them are poorly understood.…”
Section: Epigenetic Reprogramming Of Stem Cells In Uterine Fibroids Imentioning
confidence: 99%
“…Although the role of MSCs in development of UFs is extremely important, 23,32,33 the molecular mechanism underlying developmental exposure to EDCs and other toxins at MSCs levels has not been characterized before. 15 By ribonucleic acid (RNA)- sequencing analysis, we recently identified some key genes including estrogen responsive genes (ERGs) that are differentially regulated in MSCs early-life exposed to diethylstilbestrol (DES) verse control (VEH).…”
Section: Epigenetic Reprogramming Of Stem Cells In Uterine Fibroids Imentioning
confidence: 99%